2009
DOI: 10.1002/jmv.21552
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of human papillomavirus type 16 E6, E7, and L1 genes in Italian women with different grades of cervical lesions

Abstract: High-risk human papillomaviruses (HPVs) are risk factors for the development of cervical cancer. HPV 16 is the most common type, being present in about 60% of cervical cancers worldwide. Previous studies have reported upon the association between HPV 16 E6 variants and increased risk of cervical intraepithelial neoplasia and invasive cervical cancer. In this study, the presence of HPV 16 polymorphisms in the E6, E7, and L1 genes was investigated in relation to the presence of highgrade lesions. Sequencing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…We did not find association between the presence of these mutations and the severity of the lesions, in agreement to other authors like Cento et al [25] studying Italian women and Liu et al [33] studying Chinese women. In the later study, there were reported additional changes in E7 positions such as G599A (R9K), C632T (T20I), G694A (G41R), t744g, G760A (G63S), and G761A (G63D).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We did not find association between the presence of these mutations and the severity of the lesions, in agreement to other authors like Cento et al [25] studying Italian women and Liu et al [33] studying Chinese women. In the later study, there were reported additional changes in E7 positions such as G599A (R9K), C632T (T20I), G694A (G41R), t744g, G760A (G63S), and G761A (G63D).…”
Section: Discussionsupporting
confidence: 81%
“…More recently, the ICTV Papillomavirus Study Group proposed an entire genomic approach (for information on current HPV taxonomy, https://pave.niaid.nih.gov/index.html). Variants in the oncogenes E6/E7 genes and LCR have also been of interest for the potential association with disease [25,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Human Papillomavirus type 16 (HPV16) is the most prevalent oncogenic HPV type worldwide and the prevalence of its different lineages differs across geographical locations (zur Hausen 1991; Cento et al, 2009;Cornet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The latter represents a single variant among 35 HPV-16 cervical cancer or cervicitis patients analyzed. Analysis of the complete E7 open reading frame from those 35 patients revealed four nucleotide variations in three (8.5%) patients, whereas the other 32 did not contain any nucleotide changes compared with the prototype (52). Of the identified changes, two were silent nucleotide changes, and two were missense substitutions, resulting in the amino acid changes L15V and S31R.…”
Section: Generation and Characterization Of T Cell Lines-tomentioning
confidence: 99%